THE ROLE OF MSMES AND WOMEN'S EMPOWERMENT IN ECONOMIC DEVELOPMENT IN INDONESIA: LITERATURE REVIEW, ANALYSIS AND DEVELOPMENT STRATEGY - Iqbal Agustia Miransyah; Ritha Dalimunthe (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The economic development of a country is greatly influenced by the quality of human resources (HR) and the business sector developing within it, with the Micro, Small and Medium Enterprises (MSME) sector playing a strategic role in economic growth, employment and distribution of results in Indonesia. . However, MSMEs are faced with various challenges such as lack of capital, limited access to financing, and business climate conditions that are not yet conducive. This research aims to analyze the role of entrepreneurship and women's empowerment in reducing unemployment and improving the economy, identifying challenges in economic empowerment and building understanding of solutions, designing concrete strategies to increase awareness, skills and collaboration in business development and strengthening the MSME sector, encouraging the role of MSMEs in national economic development by highlighting its contribution and potential, as well as providing an understanding of the importance of entrepreneurship, women's empowerment, and the role of MSMEs in economic development, as well as formulating strategies to overcome the challenges faced . This research uses a literature review study method with a systematic approach to data analysis. The results show that efforts to empower women through MSMEs have had a positive impact on the family economy and society at large. However, there are still obstacles that need to be overcome in efforts to empower the community's economy. Concrete strategies and a holistic approach are needed to overcome these challenges and strengthen the contribution of MSMEs to national economic development.